Synthesis of multivalent host and guest molecules for the construction of multithreaded diamide pseudorotaxanes - Löw, Nora L.; Dzyuba, Egor V.; Brusilowskij, Boris; Kaufmann, Lena; Franzmann, Elisa; Maison, Wolfgang; Brandt, Emily; Aicher, Daniel; Wiehe, Arno; Schalley, Christoph A. (Beilstein Journal of Organic Chemistry, 2012)
A series of di-, tri- and tetravalent axles and wheels for the synthesis of pseudorotaxanes bearing the tetralactam macrocycle/diamide axle binding motif was prepared. Starting from iodinated monovalent precursors, Sonogashira cross-coupling reactions were utilized to couple the binding sites to appropriate spacer groups. Through this “Lego” or “toolbox” approach, the convergent synthesis of host and guests with a well-defined number of the binding sites is possible. In addition, the spatial arrangement of the binding sites can be controlled through the quite rigid connections between linker and binding sites. Although a quantitative assessment of binding strengths was not possible by NMR titration experiments, typical and significant shifts of the signals of the diamide moiety indicate qualitatively the formation of pseudorotaxanes from the axle and wheel precursors.
Keywords: multivalency; pseudorotaxanes; Sonogashira coupling; supramolecular chemistry; tetralactam macrocycles

Supramolecular Chemistry - Concepts and Perspectives - Lehn, J.-M. (Wiley-VCH, 1995)

Molecular Catenanes, Rotaxanes, and Knots - Sauvage, J.-P.; Dietrich-Buchecker, C. O. (Wiley-VCH, 1999)

Template Synthesis of Macrocyclic Compounds - Gerbeleu, N. V.; Arion, V. B.; Burgess, J. (Wiley-VCH, 1999)

Templated Organic Synthesis - Diederich, F.; Stang, P. J. (Wiley-VCH, 2000)

Core Concepts in Supramolecular Chemistry and Nanochemistry - Steed, J. W.; Turner, D. R.; Wallace, K. (Wiley-VCH, 2007)

Modern Supramolecular Chemistry: Strategies for Macrocycle Synthesis - Diederich, F.; Stang, P. J.; Tykwinski, R. R. (Wiley-VCH, 2008)

Supramolecular Chemistry - Atwood, J. L.; Steed, J. W. (Wiley, 2009)

Bottom-up Nanofabrication: Supramolecules, Self-Assemblies, and Organized Films - Ariga, K.; Nalwa, H. S. (American Scientific Publishers, 2009)

(untitled) - Mammen, M.; Choi, S.-K.; Whitesides, G. M. (Angew. Chem., 1998)
Angew. Chem., Int. Ed. 1998, 37, 2754–2794. doi:10.1002/(SICI)1521-3773(19981102)37:20<2754::AID-ANIE2754>3.0.CO;2-3

(untitled) - Mulder, A.; Huskens, J.; Reinhoudt, D. N. (Org. Biomol. Chem., 2004)

(untitled) - Kiessling, L. L.; Gestwicki, J. E.; Strong, L. E. (Angew. Chem., 2006)
Angew. Chem., Int. Ed. 2006, 45, 2348–2368. doi:10.1002/anie.200502794

(untitled) - Reczek, J. J.; Kennedy, A. A.; Halbert, B. T.; Urbach, A. R. (J. Am. Chem. Soc., 2009)

(untitled) - Sauvage, J.-P. (Acc. Chem. Res., 1998)

(untitled) - Blanco, M.-J.; Jiménez, M. C.; Chambron, J.-C.; Heitz, V.; Linke, M.; Sauvage, J.-P. (Chem. Soc. Rev., 1999)

(untitled) - Balzani, V.; Credi, A.; Raymo, F. M.; Stoddart, J. F. (Angew. Chem., 2000)
Angew. Chem., Int. Ed. 2000, 39, 3348–3391. doi:10.1002/1521-3773(20001002)39:19<3348::AID-ANIE3348>3.0.CO;2-X

(untitled) - Schalley, C. A.; Beizai, K.; Vögtle, F. (Acc. Chem. Res., 2001)

(untitled) - Ballardini, R.; Balzani, V.; Credi, A.; Gandolfi, M. T.; Venturi, M. (Acc. Chem. Res., 2001)

(untitled) - Harada, A. (Acc. Chem. Res., 2001)

(untitled) - Collin, J.-P.; Dietrich-Buchecker, C.; Gaviña, P.; Jiménez-Molero, M. C.; Sauvage, J.-P. (Acc. Chem. Res., 2001)

(untitled) - Clemente-León, M.; Credi, A.; Martínez-Díaz, M.-V.; Mingotaud, C.; Stoddart, J. F. (Adv. Mater., 2006)

(untitled) - Balzani, V.; Credi, A.; Silvi, S.; Venturi, M. (Chem. Soc. Rev., 2006)

(untitled) - Credi, A. (Angew. Chem., 2007)
Angew. Chem., Int. Ed. 2007, 46, 5472–5475. doi:10.1002/anie.200700879

(untitled) - Kay, E. R.; Leigh, D. A.; Zerbetto, F. (Angew. Chem., 2006)
Angew. Chem., Int. Ed. 2007, 46, 72–191. doi:10.1002/anie.200504313

(untitled) - Mateo-Alonso, A.; Guldi, D. M.; Paolucci, F.; Prato, M. (Angew. Chem., 2007)
Angew. Chem., Int. Ed. 2007, 46, 8120–8126. doi:10.1002/anie.200702725

(untitled) - Champin, B.; Mobian, P.; Sauvage, J.-P. (Chem. Soc. Rev., 2007)

(untitled) - Silvi, S.; Venturi, M.; Credi, A. (J. Mater. Chem., 2009)

(untitled) - Bodis, P.; Panman, M. R.; Bakker, B. H.; Mateo-Alonso, A.; Prato, M.; Buma, W. J.; Brouwer, A. M.; Kay, E. R.; Leigh, D. A.; Woutersen, S. (Acc. Chem. Res., 2009)

(untitled) - Durot, S.; Reviriego, F.; Sauvage, J.-P. (Dalton Trans., 2010)

Molecular Motors - Schliwa, M. (Wiley-VCH, 2003)

Molecular Devices and Machines. A Journey into the Nano World - Balzani, V.; Venturi, M.; Credi, A. (Wiley-VCH, 2003)

Molecular Devices and Machines: Concepts and Perspectives for the Nanoworld - Balzani, V.; Credi, A.; Venturi, M. (Wiley-VCH, 2008)

From Non-Covalent Assemblies to Molecular Machines - Sauvage, J.-P.; Gaspard, P. (Wiley-VCH, 2010)

(untitled) - Dietrich-Buchecker, C. O.; Sauvage, J.-P. (Chem. Rev., 1987)

(untitled) - Anderson, S.; Anderson, H. L.; Sanders, J. K. M. (Acc. Chem. Res., 1993)

(untitled) - Chambron, J.-C.; Collin, J.-P.; Heitz, V.; Jouvenot, D.; Kern, J.-M.; Mobian, P.; Pomeranc, D.; Sauvage, J.-P. (Eur. J. Org. Chem., 2004)

(untitled) - Amman, M.; Rang, A.; Schalley, C. A.; Bäuerle, P. (Eur. J. Org. Chem., 2006)

(untitled) - Hutin, M.; Schalley, C. A.; Bernardinelli, G.; Nitschke, J. R. (Chem.–Eur. J., 2006)

(untitled) - Bäuerle, P.; Ammann, M.; Wilde, M.; Götz, G.; Mena-Osteritz, E.; Rang, A.; Schalley, C. A. (Angew. Chem., 2007)
Angew. Chem., Int. Ed. 2007, 46, 363–368. doi:10.1002/anie.200602652

(untitled) - Yamashita, K.-i.; Kawano, M.; Fujita, M. (J. Am. Chem. Soc., 2007)

(untitled) - Meyer, C. D.; Joiner, C. S.; Stoddart, J. F. (Chem. Soc. Rev., 2007)

(untitled) - Bonnet, S.; Collin, J.-P. (Chem. Soc. Rev., 2008)

(untitled) - Crowley, J. D.; Goldup, S. M.; Lee, A.-L.; Leigh, D. A.; McBurney, R. T. (Chem. Soc. Rev., 2009)

(untitled) - Faiz, J. A.; Heitz, V.; Sauvage, J.-P. (Chem. Soc. Rev., 2009)

(untitled) - Collin, J.-P.; Durola, F.; Heitz, V.; Reviriego, F.; Sauvage, J.-P.; Trolez, Y. (Angew. Chem., 2010)

(untitled) - Clever, G. H.; Shionoya, M. (Chem.–Eur. J., 2010)

(untitled) - Megiatto, J. D., Jr; Schuster, D. I.; Abwandner, S.; de Miguel, G.; Guldi, D. M. (J. Am. Chem. Soc., 2010)

(untitled) - Hänni, K. D.; Leigh, D. A. (Chem. Soc. Rev., 2010)

(untitled) - Amabilino, D. B.; Stoddart, J. F.; Williams, D. J. (Chem. Mater., 1994)

(untitled) - Amabilino, D. B.; Stoddart, J. F. (Chem. Rev., 1995)

(untitled) - Glink, P. T.; Stoddart, J. F. (Pure Appl. Chem., 1998)

(untitled) - Nepogodiev, S. A.; Stoddart, J. F. (Chem. Rev., 1998)

(untitled) - Lee, J. W.; Samal, S.; Selvapalam, N.; Kim, H.-J.; Kim, K. (Acc. Chem. Res., 2003)

(untitled) - Kim, K.; Selvapalam, N.; Ko, Y. H.; Park, K. M.; Kim, D.; Kim, J. (Chem. Soc. Rev., 2007)

(untitled) - Dichtel, W. R.; Miljanić, O. Š.; Zhang, W.; Spruell, J. M.; Patel, K.; Aprahamian, I.; Heath, J. R.; Stoddart, J. F. (Acc. Chem. Res., 2008)

(untitled) - Griffiths, K. E.; Stoddart, J. F. (Pure Appl. Chem., 2008)

(untitled) - Isaacs, L. (Chem. Commun., 2009)

(untitled) - Appel, E. A.; Biedermann, F.; Rauwald, U.; Jones, S. T.; Zayed, J. M.; Scherman, O. A. (J. Am. Chem. Soc., 2010)

(untitled) - Zhang, M.; Zhu, K.; Huang, F. (Chem. Commun., 2010)

(untitled) - Au-Yeung, H. Y.; Pantoş, G. D.; Sanders, J. K. M. (Angew. Chem., 2010)
Angew. Chem., Int. Ed. 2010, 49, 5331–5334. doi:10.1002/anie.201000807

(untitled) - Cougnon, F. B. L.; Au-Yeung, H. Y.; Pantoş, G. D.; Sanders, J. K. M. (J. Am. Chem. Soc., 2011)

(untitled) - Fang, L.; Basu, S.; Sue, C.-H.; Fahrenbach, A. C.; Stoddart, J. F. (J. Am. Chem. Soc., 2011)

(untitled) - Biedermann, F.; Rauwald, U.; Zayed, J. M.; Scherman, O. A. (Chem. Sci., 2011)

(untitled) - Niu, Z.; Huang, F.; Gibson, H. W. (J. Am. Chem. Soc., 2011)

(untitled) - Hunter, C. A. (J. Chem. Soc., Chem. Commun., 1991)

(untitled) - Hunter, C. A. (J. Am. Chem. Soc., 1992)

(untitled) - Vögtle, F.; Meier, S.; Hoss, R. (Angew. Chem., 1992)
Angew. Chem., Int. Ed. 1992, 31, 1619–1622. doi:10.1002/anie.199216191

(untitled) - Ottens-Hildebrandt, S.; Meier, S.; Schmidt, W.; Vögtle, F. (Angew. Chem., 1994)
Angew. Chem., Int. Ed. 1994, 33, 1767–1770. doi:10.1002/anie.199417671

(untitled) - Vögtle, F.; Dünnwald, T.; Schmidt, T. (Acc. Chem. Res., 1996)

(untitled) - Kim, K. (Chem. Soc. Rev., 2002)

(untitled) - Schalley, C. A.; Weilandt, T.; Brüggemann, J.; Vögtle, F. (Top. Curr. Chem., 2004)

(untitled) - Kay, E. R.; Leigh, D. A. (Top. Curr. Chem., 2005)

(untitled) - Jiang, W.; Winkler, H. D. F.; Schalley, C. A. (J. Am. Chem. Soc., 2008)

(untitled) - Jiang, W.; Schalley, C. A. (Proc. Natl. Acad. Sci. U. S. A., 2009)

(untitled) - Stoddart, J. F. (Chem. Soc. Rev., 2009)

(untitled) - Lee, C.-F.; Leigh, D. A.; Pritchard, R. G.; Schultz, D.; Teat, S. J.; Timco, G. A.; Winpenny, R. E. P. (Nature, 2009)

(untitled) - Jiang, W.; Mohr, P. C.; Schäfer, A.; Schalley, C. A. (J. Am. Chem. Soc., 2010)

(untitled) - Jiang, W.; Schalley, C. A. (Beilstein J. Org. Chem., 2010)

(untitled) - Fang, L.; Olson, M. A.; Benítez, D.; Tkatchouk, E.; Goddard, W. A., III; Stoddart, J. F. (Chem. Soc. Rev., 2010)

(untitled) - Ma, X.; Tian, H. (Chem. Soc. Rev., 2010)

(untitled) - Jiang, W.; Han, M.; Zhang, H.-Y.; Zhang, Z.-J.; Liu, Y. (Chem.–Eur. J., 2009)

(untitled) - Chen, C.-F. (Chem. Commun., 2011)

(untitled) - Badjić, J. D.; Nelson, A.; Cantrill, S. J.; Turnbull, W. B.; Stoddart, J. F. (Acc. Chem. Res., 2005)

(untitled) - Badjić, J. D.; Balzani, V.; Credi, A.; Silvi, S.; Stoddart, J. F. (Science, 2004)

(untitled) - Badjić, J. D.; Ronconi, C. M.; Stoddart, J. F.; Balzani, V.; Silvi, S.; Credi, A. (J. Am. Chem. Soc., 2006)

(untitled) - Reuter, C.; Vögtle, F. (Org. Lett., 2000)

(untitled) - Affeld, A.; Hübner, G. M.; Seel, C.; Schalley, C. A. (Eur. J. Org. Chem., 2001)

(untitled) - Schalley, C. A.; Silva, G.; Nising, C.-F.; Linnartz, P. (Helv. Chim. Acta, 2002)

(untitled) - Li, X.-y.; Illigen, J.; Nieger, M.; Michel, S.; Schalley, C. A. (Chem.–Eur. J., 2003)

(untitled) - Linnartz, P.; Bitter, S.; Schalley, C. A. (Eur. J. Org. Chem., 2003)

(untitled) - Felder, T.; Schalley, C. A. (Angew. Chem., 2003)
Angew. Chem., Int. Ed. 2003, 42, 2258–2260. doi:10.1002/anie.200350903

(untitled) - Linnartz, P.; Schalley, C. A. (Supramol. Chem., 2004)

(untitled) - Ghosh, P.; Federwisch, G.; Kogej, M.; Schalley, C. A.; Haase, D.; Saak, W.; Lützen, A.; Gschwind, R. M. (Org. Biomol. Chem., 2005)

(untitled) - Seel, C.; Parham, A. H.; Safarowsky, O.; Hübner, G. M.; Vögtle, F. (J. Org. Chem., 1999)

(untitled) - Chang, S.-Y.; Kim, H. S.; Chang, K.-J.; Jeong, K.-S. (Org. Lett., 2004)

(untitled) - Herrmann, U.; Jonischkeit, T.; Bargon, J.; Hahn, U.; Li, Q.-Y.; Schalley, C. A.; Vogel, E.; Vögtle, F. (Anal. Bioanal. Chem., 2002)

(untitled) - Bargon, J.; Braschoß, S.; Flörke, J.; Herrmann, U.; Klein, L.; Lörgen, J. W.; Lopez, M.; Maric, S.; Parham, A. H.; Piacenza, P.; Schäfgen, H.; Schalley, C. A.; et al. (Sens. Act. B, 2003)

(untitled) - Kleefisch, G.; Kreutz, C.; Bargon, J.; Silva, G.; Schalley, C. A. (Sensors, 2004)

(untitled) - Kossev, I.; Reckien, W.; Felder, T.; Kishan, M. R.; Schalley, C. A.; Sokolowski, M. (J. Phys. Chem. C, 2009)

(untitled) - Kossev, I.; Reckien, W.; Kirchner, B.; Felder, T.; Nieger, M.; Schalley, C. A.; Vögtle, F.; Sokolowski, M. (Adv. Funct. Mater., 2007)

(untitled) - Kossev, I.; Felder, T.; Schalley, C. A.; Vögtle, F.; Sokolowski, M. (Springer Proc. Phys., 2009)

(untitled) - Hunter, C. A.; Packer, M. J. (Chem.–Eur. J., 1999)

(untitled) - Chinchilla, R.; Nájera, C. (Chem. Rev., 2007)

(untitled) - Baytekin, B.; Zhu, S. S.; Brusilowskij, B.; Illigen, J.; Ranta, J.; Huuskonen, J.; Russo, L.; Rissanen, K.; Kaufmann, L.; Schalley, C. A. (Chem.–Eur. J., 2008)

(untitled) - Dzyuba, E. V.; Baytekin, B.; Sattler, D.; Schalley, C. A. (Eur. J. Org. Chem.)

(untitled) - Liu, H.-X.; Shao, F.; Li, G.-Q.; Xun, G.-L.; Yao, Z.-J. (Chem.–Eur. J., 2008)

(untitled) - Kabalka, G. W.; Wang, L. (Tetrahedron Lett., 2002)

(untitled) - Kuo, M.-C.; Li, L.-A.; Yen, W.-N.; Lo, S.-S.; Lee, C.-W.; Yeh, C.-Y. (Dalton Trans., 2007)

(untitled) - Ljungdahl, T.; Bennur, T.; Dallas, A.; Emtenäs, H.; Mårtensson, J. (Organometallics, 2008)

(untitled) - Maison, W.; Frangioni, J. V.; Pannier, N. (Org. Lett., 2004)

(untitled) - Pannier, N.; Maison, W. (Eur. J. Org. Chem., 2008)

(untitled) - Spickermann, C.; Felder, T.; Schalley, C. A.; Kirchner, B. (Chem.–Eur. J., 2008)

(untitled) - Dzyuba, E. V.; Kaufmann, L.; Löw, N. L.; Meyer, A. K.; Winkler, H. D. F.; Rissanen, K.; Schalley, C. A. (Org. Lett., 2011)